2021
DOI: 10.7717/peerj-cs.444
|View full text |Cite
|
Sign up to set email alerts
|

Neural network hyperparameter optimization for prediction of real estate prices in Helsinki

Abstract: Accurate price evaluation of real estate is beneficial for many parties involved in real estate business such as real estate companies, property owners, investors, banks, and financial institutes. Artificial Neural Networks (ANNs) have shown promising results in real estate price evaluation. However, the performance of ANNs greatly depends upon the settings of their hyperparameters. In this paper, we apply and optimize an ANN model for real estate price prediction in Helsinki, Finland. Optimization of the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In deep learning, there are several hyperparameters that become variables that will affect model output, determine training details and significantly influence model performance [39]- [41]. In this study, three hyperparameter tuning experiments were carried out and can be shown in Table 1.…”
Section: Results Of Hyperparametermentioning
confidence: 99%
“…In deep learning, there are several hyperparameters that become variables that will affect model output, determine training details and significantly influence model performance [39]- [41]. In this study, three hyperparameter tuning experiments were carried out and can be shown in Table 1.…”
Section: Results Of Hyperparametermentioning
confidence: 99%
“…The hedonic price approach is widely employed in the literature to relate anomalous events and price changes. Several techniques have also been employed in the literature to understand the marginal contribution that building features (construction and neighbourhood) bring to the formation of the market price, such as spatial analysis, GIS (geographic information system), and, again, hedonic price regressions and neural networks [43,44].…”
Section: A Diachronic Analysis Related To Major Anomalous Eventsmentioning
confidence: 99%
“…16. Jussi Kalliola, et al [78] Suggested an ANN optimization model for real estate price prediction. To handle the nonlinear problem of real estate price prediction without under-and over-fitting problems, a multilayer perceptron (MLP) NN model utilized, along with fine-tuning hyperparameters in Helsinki, Finland.…”
Section: Applications Used Hyperparameters Optimization Algorithmsmentioning
confidence: 99%
“…The second problem accurse is filling in local minimum the most active hyperparameter in this case is momentum coefficient just like problem that showed in [73]. In [4], [78], [81], [83] the batch size hyper parameter was improved since it represents the number of the samples that have been processed prior to updating the model and the number of the complete passes through the whole training dataset in cases of a large dataset. Furthermore, the learning algorithm's dynamics are influenced by an important hyperparameter.…”
mentioning
confidence: 99%